2016
DOI: 10.24839/2164-8204.jn21.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Reliability and Convergent Validity of IPARTheory Measures

Abstract: As I write these lines, Psi Chi Journal of Psychological Research has fully transitioned to the editorial stew ardship of Dr. Debi Brannan. It is a bittersweet time; I treasured deeply the tasks of editing the Psi Chi Journal. For nearly 5 years, I benefitted from reading cuttingedge research in broad topics across psy chology. I was inspired by the knowledge that most of the authors were upandcoming researchers whose sense of efficacy could be nurtured through a positive publication experience. I reveled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In Khaleque and Rohner's (2002b) meta analysis, they reported mean alphas ranging from .78 to .91 for the subscales and total PARQ scores across cultures. Faherty et al (2016) also found the PARQ to have good reliability, with Cronbach's alphas of .76 to .87 for the subscales, and .94 to .96 for the measure as a whole. In terms of con vergent validity, the PARQ's Warmth/Affection subscale (i.e., perceived coldness) has been shown to strongly correlate with another acceptance measure, and the Hostility/Aggression subscale to correlate with physical punishment (Rohner & Khaleque, 2005, p. 61).…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…In Khaleque and Rohner's (2002b) meta analysis, they reported mean alphas ranging from .78 to .91 for the subscales and total PARQ scores across cultures. Faherty et al (2016) also found the PARQ to have good reliability, with Cronbach's alphas of .76 to .87 for the subscales, and .94 to .96 for the measure as a whole. In terms of con vergent validity, the PARQ's Warmth/Affection subscale (i.e., perceived coldness) has been shown to strongly correlate with another acceptance measure, and the Hostility/Aggression subscale to correlate with physical punishment (Rohner & Khaleque, 2005, p. 61).…”
Section: Methodsmentioning
confidence: 85%
“…These include (a) trouble managing anger, (b) dependence or defensive independence, (c) poor selfesteem, (d) reduced selfadequacy, (e) unstable emotions (e.g., reduced ability to manage stress), (f) emotional unresponsiveness (e.g., trouble giving and receiving love), and (g) negative worldview (e.g., believing the world to be a dangerous place; Rohner & Khaleque, 2002;Rohner & Rising, 2006). In a metaanalysis of 30 studies, Khaleque (2013) found, with strong effect sizes, that these personality dispositions held true across cultures, as did Faherty, Eagan, Ashdown, Brown, and Hanno (2016) in their study of perceived parental rejection in Guatemala. Moreover, these personality disposi tions lead to a reduced capacity to deal with stress ("Ronald P. .…”
Section: Interpersonal Acceptance-rejection Theorymentioning
confidence: 86%
See 1 more Smart Citation
“…These include (a) trouble managing anger, (b) dependence or defensive independence, (c) poor selfesteem, (d) reduced selfadequacy, (e) unstable emotions (e.g., reduced ability to manage stress), (f) emotional unresponsiveness (e.g., trouble giving and receiving love), and (g) negative worldview (e.g., believing the world to be a dangerous place; Rohner & Khaleque, 2002;Rohner & Rising, 2006). In a metaanalysis of 30 studies, Khaleque (2013) found, with strong effect sizes, that these personality dispositions held true across cultures, as did Faherty, Eagan, Ashdown, Brown, and Hanno (2016) in their study of perceived parental rejection in Guatemala. Moreover, these personality disposi tions lead to a reduced capacity to deal with stress ("Ronald P. acceptancerejection syndrome is additionally associated with less resilience, because resilience is positively associated with selfesteem (Mizuno et al 2016), selfefficacy (Smith et al, 2008), and by definition, stress management (Fletcher & Sarkar, 2013).…”
Section: Interpersonal Acceptance-rejection Theorymentioning
confidence: 87%